(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Recording of Death and its causes constitute an important component of health information system. The study was conducted on 90 hospital deaths during the period of six months from July-December of 2017, at Great Eastern Medical School and Hospital. Males more than 60 years of age group were the major victims in our study. Improving primary health care facilities in rural areas may reduce the Mortality and Morbidity.